2016
DOI: 10.1159/000445689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyperbaric Oxygen Therapy on Inflammasome Signaling after Traumatic Brain Injury

Abstract: Objective: Neuroinflammation plays an important role in secondary tissue damage after traumatic brain injury (TBI). Recently, the inflammasome-mediated inflammatory pathway has been observed in the inflammatory response of TBI. In this study, we investigated the influence of hyperbaric oxygen therapy (HBOT) on inflammasome activation after TBI. Methods: The experimental mice were randomly divided into 4 groups as follows: sham-operated normobaric air (21% O2 at one absolute atmosphere), HBOT only, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 27 publications
(34 reference statements)
0
19
0
Order By: Relevance
“…The key to clinical treatment is to address the above factors that cause brain damage, prevent or alleviate further damage and promote recovery. The following are the main treatment strategies [51,[101][102][103][104][105]. 1) Rapid and effective cooling is the most important measure for alleviating injury to the central nervous system, and a faster cooling rate is more beneficial for the prognosis of HS patients.…”
Section: Central Nervous System Injury and Brain Protectionmentioning
confidence: 99%
“…The key to clinical treatment is to address the above factors that cause brain damage, prevent or alleviate further damage and promote recovery. The following are the main treatment strategies [51,[101][102][103][104][105]. 1) Rapid and effective cooling is the most important measure for alleviating injury to the central nervous system, and a faster cooling rate is more beneficial for the prognosis of HS patients.…”
Section: Central Nervous System Injury and Brain Protectionmentioning
confidence: 99%
“…Harch et al [7] treated 16 TBI, post-TBI syndrome, and posttraumatic stress disorder (PTSD) patients with 40 sessions of 1.5 ATA/60 minutes of HBOT for 30 days, which greatly improved symptoms, results of neurological examinations, comprehensive IQ tests, and cognition functions. A study by Geng et al [8] showed that HBOT may suppress activation of inflammasome signals, thereby alleviating TBI.…”
Section: Hyperbaric Oxygen Therapy (Hbot) Relieves Tbimentioning
confidence: 99%
“… 108 , 123 In addition, the expression of the group of proteins that comprise the inflammasome was also shown to be increased following TBI and reduced after subsequent HBOT. 121 These studies help provide support for an important influence of HBOT over the inflammatory response in acute TBI.…”
Section: Possible Mechanisms Of Actionmentioning
confidence: 87%